Study of radiation-stimulated structural phase transformations in iradiated Zr by Mössbauer spectroscopy - Tolen, D.E.; Vereshchak, М.F.; Shokanov, A.K.; Manakova, I.A.; Tleubergenov, J.K. (Recent Contributions to Physics, 2022)
The article considers the study of the influence of high-energy singly charged 57Fe ions with energy of 1 MeV, a beam current on the target of ~100 nA, a dose of 5x1016 ion/cm2, on the structural-phase state of zirconium. Using the methods of Mössbauer spectroscopy in transmission geometry (MS), conversion electron Mössbauer spectroscopy (CEMS), and scanning electron microscopy (SEM), we studied the effect of high-energy singly charged 57Fe ions on the structural-phase state of zirconium. The projective ranges of 57Fe ions in zirconium were determined, the number of target atoms subjected to irradiation was calculated, and the number of displacements caused by these ions was estimated. Radiation damage to zirconium materials was simulated by irradiating samples at a charged particle accelerator with probe Mössbauer atoms to obtain nuclear physical data from the zone of influence of these atoms on the structural and phase state of irradiated samples under conditions close to reactor conditions. The electronic state of the implant in these materials was evaluated. The concentration of implanted atoms in the near-surface layer and the volume of samples was calculated. In particular, it was shown that the projective range of 57Fe ions in zirconium was 497 nm, the total number of displaced atoms was 3.4х1020, and the number of displacements per atom (dpa) was 159. The solubility of Fe in Zr is 0.03%. However, when zirconium is irradiated with 57Fe ions, as a result of thermal recombination of vacancies and interstitial atoms within the cascade of displacements caused by thermal peaks, intermetallic compounds Zr3Fe, ZrFe2 and a Zr (Fe) solid solution are formed.